A Meridione dell’Urbe. Il palazzo comitale nei feudi Caetani agli inizi del Trecento - Pistilli, Pio Francesco (Opus Incertum, 2016)
This paper focuses on the origins of the baronial palaces to the south of Rome in the early fourteenth century, looking atexemplary cases which are based on models commissioned by the House of Anjou (see the residences of Charles I of Anjouin Mola di Bari and Villanova di Ostuni, perfectly documented in the registry of the Curia regia) and which found in thepatronage of Roffredo Caetani their diffusion to the northern territories of the Kingdom in the bordering Pontifical region of Marittima.